Quality of life of Asthmatic Adult Patient's in Kirkuk city - Rebaz Ismail Ali (College of Nursing,University of Mosul, 2015)
Background and objectives: Asthma is a life-long chronic inflammatory disorder of the airways, associated with variable structural changes, that affects all ages. Health related quality of life (HRQoL) has joined morbidity and mortality as a health outcome of interest in recent years. The study objected to assess quality of life for asthmatic patients and to predict the correlations among the domains of quality of life. Materials and method: A descriptive study was conducted in Kirkuk General Hospital in Kirkuk city to assess the Quality of Life (QoL) asthmatic patients , and to identify the association between some characteristics of asthmatic patients such as (Age, Gender, Martial status, Level of education, Occupation and Severity of asthma ) and their quality of life. The study was initiated from 20 of June 2013 to 5th May 2014. Purposive sample consists of (70) patients with asthma were selected. For the purpose of data collection, a questionnaire was constructed instrument and literature reviews. It is composed of two parts, part one included (9) items that focused on the client demographic characteristics. Part two is composed of (5) items that contain of (98) items, data were collected through the use of interview. Of 3-likert scale option as: (1) for Always, (2) for Sometimes and (3) for Never. Content validity was determined by presenting the questionnaire to a panel of (8) experts. Results: The findings of the study indicated that the sub-domain of sleep and rest as a part the physical domain, also the spiritual domain of the quality of life for patients had greatly affected. Conclusion: The study concluded that found significant statistical of some of socio -demographics characteristic of asthma patients (Educational level and Severity of asthma ) with domains of the quality of life. Also, associations between the physical and spiritual domains Recommendations: The study recommends to increase the number of specialized health related agencies and asthma units and to enhancing the community and social support of patients. Keywords: Quality of Life, Adult Asthmatic patients.